2006
DOI: 10.4049/jimmunol.177.12.8806
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase Regulates Cell Surface Expression of CXCR3/1-Storing Granules in Human CD4+ T Cells

Abstract: Efficient migration of CD4+ T cells into sites of infection/inflammation is a prerequisite to protective immunity. Inappropriate recruitment, on the other hand, contributes to inflammatory pathologies. The chemokine/chemokine receptor system is thought to orchestrate T cell homing. In this study, we show that most circulating human CD4+ T cells store the inflammatory chemokine receptors CXCR3 and CXCR1 within a distinct intracellular compartment. Equipped with such storage granules, CD4+ T cells coexpressing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…We subsequently turned our attention to the fate of CXCR3 following its internalization, using confocal microscopy to examine intracellular localisation of the receptor in permeablized T-lymphocytes. A predominantly granular intracellular staining pattern for CXCR3 was evident in untreated cells, (Figure 6A) identical to that previously described by Gasser and colleagues (44). Likewise, a similar pattern was seen for staining with the late endosome marker lamp-1 (Figure 6B) with little co-localisation of signals seen (Figure 6C).…”
Section: Resultssupporting
confidence: 86%
“…We subsequently turned our attention to the fate of CXCR3 following its internalization, using confocal microscopy to examine intracellular localisation of the receptor in permeablized T-lymphocytes. A predominantly granular intracellular staining pattern for CXCR3 was evident in untreated cells, (Figure 6A) identical to that previously described by Gasser and colleagues (44). Likewise, a similar pattern was seen for staining with the late endosome marker lamp-1 (Figure 6B) with little co-localisation of signals seen (Figure 6C).…”
Section: Resultssupporting
confidence: 86%
“…Known as a chemoattractant for neutrophils, CXCL8 can also recruit T cells, particularly activated or effector/memory T cell types 36 37 . The role of CXCL8 in the pathogenesis of OLP requires further study because there are conflicting reports regarding its expression in OLP tissues 21 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies demonstrated that resting human T cells expressed little CXCR3, but this receptor was expressed by the majority of T cells after mitogenic activation for 72 h by culturing with the immobilised CD3 antibody, OKT3. Indeed, previous studies have shown that CXCR3 is stored by resting T cells in cytoplasmic granules allowing release onto the cell-surface within minutes of activation (Gasser et al, 2006). This chemokine receptor was shown to function in transendothelial chemotaxis assays in which the ligand CXCL10 was added below the endothelial cell monolayer.…”
Section: Discussionmentioning
confidence: 99%